2013
DOI: 10.1159/000354807
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Molsidomine against Doxorubicin-Induced Cardiotoxicity in Rats

Abstract: Purpose: To explore the protective and curative effects of molsidomine (MOL) on doxorubicin (DOX)-induced cardiac damage in the in vivo rat heart. Methods: Forty rats were randomized into five groups (n = 8): (1) the control group; (2) the MOL group (10 mg/kg for 21 days); (3) the DOX group (a single dose of 20 mg/kg); (4) the DOX + MOL group (3 days after the single dose of DOX, 10 mg/kg MOL continued for 21 days), and (5) the MOL + DOX group (24 h after a 21-day regimen of 10 mg/kg MOL, a single dose of DOX)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…In continuation of our interest in sydnone derived carbenes 45 we report here on N-heterocyclic carbenes of two sydnone imines, among those the carbene of Molsidomine. This orally active vasodilating drug for the prevention of angina pectoris attacks 47 is the subject of intense ongoing pharmacological research, [48][49][50][51][52] however, during the last decade not much effort has been directed toward its chemical properties. We present some surprising results in the light of the relationship between mesomeric betaines and Nheterocyclic carbenes.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…In continuation of our interest in sydnone derived carbenes 45 we report here on N-heterocyclic carbenes of two sydnone imines, among those the carbene of Molsidomine. This orally active vasodilating drug for the prevention of angina pectoris attacks 47 is the subject of intense ongoing pharmacological research, [48][49][50][51][52] however, during the last decade not much effort has been directed toward its chemical properties. We present some surprising results in the light of the relationship between mesomeric betaines and Nheterocyclic carbenes.…”
Section: A R T I C L E I N F O Abstractmentioning
confidence: 99%
“…11 In comparison to sydnones, much less is known about sydnone imines. Concerning the biological activity, the NO donor and vasodilating drug Molsidomine (Corvasal, Corvaton, Molsidain, Molsidolat), however, is a prominent and widely applied sydnone imine to which interest has been directed with respect to antiarrhythmogenic, 12 anxiolytic, 13 cardioprotective, 14 and cerebral vasospasm-associated activities. 15 Sydnone methides are extremely rare and, to the best of our knowledge, no information is available concerning the biological activities.…”
Section: Introductionmentioning
confidence: 99%
“…Rodriguez-Pena et al showed MOL reduced plasma levels of pro-inflammatory cytokines however it increases the levels of antiinflammatory cytokines in rats [26]. Taking into consideration the reduced oxidative damage caused by MOL treatment, all investigators attributed the protective actions of MOL to its antioxidative and anti-inflammatory activities [27].…”
Section: Discussionmentioning
confidence: 99%
“…MOL is transformed into the metabolite 3-morpholinosydnonimine (SIN-1), which spontaneously liberates nitric oxide (NO). Apart from its anti-anginal effects, it has been more recently reported that MOL exerts potent antioxidant, antiapoptotic and antiinflammatory effects [11][12][13]. Therefore, MOL treatment can exert beneficial effects against CIO which regarding with oxidative stress and production of excessive reactive radicals.…”
Section: Introductionmentioning
confidence: 99%